WORKLOAD AND EMOTIONAL INTELLIGENCE OF NURSES IN THE PARTITION ROOM OF SUNAN KUDUS ISLAMIC HOSPITAL - Edi Wibowo Suwandi; Dina Afifatul Ma'rufah; Muhammad Purnomo; Sri Siska Mardiana; Ifa Nailatul Iza ((IJP) Indonesia Jurnal Perawat, 2024)
Health workers dedicate themselves to the health sector, have knowledge, skills and education, and require authority to carry out health efforts (Law No. 36 of 2009). Increasing health costs should be balanced with efforts to improve the quality of health services, especially for health workers in hospitals. Knowing the relationship between nurse workload and nurses' emotional intelligence in the inpatient room at Sunan Kudus Islamic Hospital. This research uses a cross-sectional quantitative research approach; the independent variable is workload, and the dependent variable is emotional intelligence. The location is in the RSI Kudus inpatient room, with a total sample of 66 nurses, with side sampling probability sampling based on the inclusion and exclusion criteria. Time of research in June 2022. The instruments used are the Emotional Intelligence Questionnaire courtesy of NHS London. Data analysis using tests spearman rho. Spearman Rho test obtained P value = 0.027 0.05 and has a correlation coefficient value of -0.272, which means that the strength correlation/relationship between workload and emotional intelligence is reasonably strong and has a negative relationship direction. There is a Relationship between Workload and the Emotional Intelligence of Nurses in the Inpatient Room at Sunan Kudus Islamic Hospital. Increasing the number of nurses per room is necessary to minimize the high workload.